PUBLIC POLICY ANALYSIS ON EDUCATION BUDGET ALLOCATION: CASE STUDY IN THIRTY-EIGHT REGENCIES/MUNICIPALITIES IN EAST JAVA, INDONESIA - Fardini Sabilah; Suparto suparto; Salahudin Salahudin (Jurnal Studi Pemerintahan, 2022)
The objective of the current study is to map regency and Municipality government budget allocations in East Java Province, Indonesia. The study uses quantitative and qualitative approaches. The quantitative approach is related to the use of numerical data on the percentage of education budget allocations. The qualitative approach is related to the use of interview data obtained from the head of the regency/Municipality Education Office in East Java Province. The study reveals that there are 5 (five) education budget allocation clusters in East Java, namely cluster A with the highest percentage of education budget allocation, covering Jember Regency and Nganjuk Regency, whereas Clusters B, C, D, and E are regencies/Municipalities with the medium, smallest, and lowest percentage of education budget allocations. Since there are only two regencies/Municipalities categorized into cluster A, it indicates that the 20% target allocation of the national education budget policy is still far from expectations, which might be caused by the planning problems, technical implementation guidelines, allocations, and different interests and perceptions among stakeholders. The limitation of this study is the use of limited qualitative data; therefore, it is expected that further research could use richer qualitative data, such as using interviews with the Regional House of Representative (DPRD) politicians, political parties, education actors, and regional principals.